(untitled) (European Journal of Education and Psychology, 2019)
Low perceived self–efficacy (SE) for responding to school–related situations is posited to be associated with school refusal. This study examined the validity and reliability of the Malay version of the Self–Efficacy Questionnaire for School Situations (SEQ–SS) among early adolescents in Kota Bharu. The English version of the 25–item SEQ–SS was translated into Malay. Employing a cross–sectional design, students (10-11 years) from five randomly selected public primary schools were recruited via proportionate cluster sampling. Two hundred and fifteen students, 65% female, mean age of 10.3 years (SD=0.5), completed the Malay SEQ–SS. Validity was examined with exploratory factor analysis (EFA). Cronbach’s alpha was used to determine internal consistency. Means and standard deviations were used to describe the total and subscale scores. EFA analyses retained 19 items which clustered into four factors: ‘SE in socially challenging situations’, ‘SE in personally challenging situations’, ‘SE in separation situations’, and ‘SE in situations of disengagement from school’. Internal consistencies were low, approaching moderate, with Cronbach’s alpha values between 0.64 and 0.69. The four–factor solution of the Malay SEQ–SS appears to permit identification of specific domains of low SE which could inform individualized interventions targeting early adolescents in primary school.